An investigation to the mechanism of the electrorheological behaviors of waxy oils. (10th August 2021) - Chen, Chaohui; Zhang, Jinjun; Xie, Yiwei; Huang, Qian; Ding, Yifei; Zhuang, Yu; Xu, Miaomiao; Han, Shanpeng; Li, Zixin; Li, Hongying
Graphical abstract: Highlights: Electric field induces charged particles to adsorb on the surface of wax particles. The impedance of a waxy oil below the WAT increases after exposure to electric field. The impedance increase is positively correlated with viscosity reduction. Abstract: Previous studies have shown that the application of a high-voltage electric field to a liquid or gelled waxy crude oil can significantly improve its cold flowability, such as reducing viscosity and yield strength. However, the mechanism of the electrorheological behaviors of waxy oils remains largely unknown. In this study, the impedance spectroscopy was firstly used to investigate the mechanism of the electrorheological behaviors of waxy oils. The impedance of the waxy oil increases and the conductivity decreases after an oil is exposed to electric fields. Based on this finding and with the aid of further experiments using model oils of controlled compositions, i.e. to control the absence of wax, resins and asphaltenes in the oil, interfacial polarization of wax particles was demonstrated as the primary and essential mechanism of the electrorheological behaviors. The interfacial polarization of wax particles means that charged colloidal particles in the oil, i.e., resins and asphaltenes, would accumulate on the surface of wax particles upon the application of the external electric field, and the resulted electrostatic repulsion will diminish the van der Waals force between wax particles, thus reducing viscosity and the strength of wax particle structure.